THE SOCIOLOGY OF ISLAM AS A PROBLEMATIC - Fatih AMAN (Fırat University, 2019)
With its blurred image Sociology of Islam having always discussions from the name and the subject to the method and the approach has a problamatic structure today. It is may be said that the most important reason of this situation is its newly being in establishment phase. Especially while New Religious Movements’ being a popular topic in the West is setting off the discussions of The Sosciology of Islam, increaisng of the influence of Post-modern paradigm has made it a problematic discussion. In this article, we aim to indicate the broad lines of the framework of The Sociology of Islam in the context of discussions on the points mentioned above. We suggest these names; Sociology of Islam, Islamic Sociology, Islamist Sociology, Depth Sociology, Sociology of Wisdom. When we look at its topic we can say that it is not complex. It is a different point of view in here that Sociology of Islam can be applied to the other societies apart from the Müslims. Although it is referred to the new methodology approaches in the title of metadology, in this sense, we think that rationality of the methodology will benefit from the methodology of social science methodology. According to the name, subject and methodology it is clear that there are some approaches forming the social sciences. In this study, the main determinant issue is the title of 'approach' and the basis of the Sociology of Islam discussions are also focused on here. As an extension of separation of Religion-Science, the Fact-Value dichotomy makes it necessary to emphasize on the approach. The lack of text, according to us is the weakest point of the sociology of Islam, is discussed in the last title. The general framework we reach on the upshot is our thought and it is not an accuracy expression by all means.